PENGUATAN INFRASTRUKTUR DAN EDUKASI MASYARAKAT DESA PUNGGUR KECIL MENUJU MASYARAKAT YANG BERPENDIDIKAN, KREATIF, DAN INOVATIF - Iwande, Fransiskus Paskha; Rizal, Maulana Filani; Ariffin, Muchammad (LPPM Universitas Panca Bhakti, 2024)
Punggur Kecil Village has great potential in social and economic development, but is hampered by inadequate infrastructure and limited access to education, which hinders the creativity and innovation of the community. This community service programme aims to address these issues by improving village infrastructure and providing participatory education that encourages a creative and innovative mindset. The programme went through four main stages: needs identification, infrastructure improvement, participatory education, and monitoring and evaluation. Needs identification was conducted through surveys and discussions with community leaders to determine intervention priorities. Infrastructure improvement focused on improving public facilities and social economic facilities, with active community participation. Participatory education was conducted through workshops and training to develop entrepreneurial skills, local product processing, and the importance of education. Programme results show significant improvements in accessibility, economic activity and community skills. Improved infrastructure facilitated the distribution of agricultural products and strengthened social ties, while education fostered entrepreneurial initiatives and innovative mindsets. Monitoring and evaluation of the programme demonstrated its success in creating a more independent, educated and competitive community, providing a sustainable impact and strengthening the capacity of Punggur Kecil Village to face future challenges